Resistansi tokoh-tokoh dalam novel sebuah lagu untuk tuhan karya agnes davonar - Apriliani, Ratih Dewi; Hartati, Dian; Adham, M. Januar Ibnu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to describe the resistance that characters do to other characters (other people) which is shown through the forms of open resistance and closed resistance in the novel A Song for God by Agnes Davonar. This resistance is very important and needed to encourage students' intelligence in developing themselves (attitudes and traits). As well as to increase knowledge, so that students can take lessons or messages contained about life problems or existing life problems (life problems). The subject of this research is the novel A Song for God by Agnes Davonar published by Inti Publisher. This novel tells about the struggle of a deaf girl with all the problems of her life. A Song for God by Agnes Davonar is included in the type of popular novel. A light novel for readers to read and enjoy. The method used in this research is descriptive analysis method. The data collection technique was carried out with library techniques. The results of the research in the novel A Song for God are that there are two resistances, namely open resistance and closed resistance.